Girls growing up on the autism spectrum : what parents and professionals should know about the pre-teen and teenage years - Nichols, Shana (Jessica Kingsley Publishers, 2009)
This book is not only reassuring; it is inspiring, and bursting with ideas and achievable strategies. The authors write with authority and conviction, and tackle even the most difficult and delicate of topics. If ever you needed to be convinced that girls with ASD can overcome the difficulties and challenges of puberty and adolescence, have successful friendships and relationships and enjoy a healthy sexuality, then take the time to read this book-it is a must-have for families, teachers and therapists alike."--Sarah Attwood, author of Making Sense of Sex: A Forthright Guide to Puberty